Ethnicity and Human Rights: Finding out a linkage in conflict and conflict resolution - Kalam Azad, Abul; Andusamadov, Abdusabur; Colmenares Olivar, Ricardo; Devi Pokhrel, Ambika; Wijegoonawardana, Nirmali (Frónesis)
The purpose of this paper is to establish a kind of linkage between human rights and minority groups. The paper consists of three principal chapters divided into a few sub-sections. Chapter I deals with a few theoretical reflections on the concepts of ethnicity and human rights. The discussion on ethnicity includes the indigenous peoples because they possess the same traits observed in the case of ethnic minorities. In addition, there have been efforts in recent times to bring this group within the purview of human rights. Chapter II, of an empirical nature, deals with the above-mentioned case studies to show that violation of a few important elements of human rights is both an actual and potential cause ofethnic conflict. Chapter III seeks to throw light on the mechanisms of conflict resolution undertaken to mitígate the conflicts mentioned in the case studies. The paper concludes that if violation of human rights is the actual or potential cause of ethnic conflicts, then conflict resolution is mademuch easier by addressing the human rights issues. In this sense, addressing multivarious human rights issues would act as a kind of preventive measure for arresting conflicts.